Implementation of Meniran Extract (Phyllanthus Niruri Linn) on the Performance of Broiler Chickens Infected by Mycoplasma gallisepticum Caused Chronic Respiratory Disease - Hidanah, Sri; Sabdoningrum, Emy Koestanti; Wahjuni, Retno Sri; Arimbi, Arimbi (KnE Life Sciences, 2017)
Chronic respiratory disease (CRD) of chicken is a disease that has great economic losses in poultry industry in the world. The losses are mainly due to the decrease of body weight gain, feed efficiencies, hatchabilities and increase conversion of the feed, of embryo mortality. The main causative agent of Chronic Respiratory Disease (CRD) is Mycoplasma gallisepticum. Mycoplasma gallisepticum attacks the respiratory tract, especially in young broiler chickens with age ranged 3-5 weeks. CRD treatment usually uses macrolide antibiotics, because it has proven effective to inhibit protein synthesis. However, it is not recommended to continuously given because the chicken can be resistant to the medicineand leave a harmful reside to consumers. The development of herbal medicine utilization currently is mostly implemented for the treatment of diseases that infected livestock. Meniran plants (Phyllanthus niruri Linn) is one of the plants that can be used as prevention and alternative treatment caused by Chronic Respiratory Disease (CRD). Meniran (Phyllanthus niruri Linn) has the content of bioactive compounds that have antibacterial activity, including terpenoids,alkaloids, flavonoids, saponins, and tannins. The purpose of this study is to test and evaluate the effectiveness of Meniran extract (Phyllanthus Niruri Linn) on the performance of broiler chickens infected by Chronic Respiratory Disease (CRD), seen from the feed conversion. Keywords: Meniran, Mycoplasma galisepticum, Chronic Respiratory Disease (CRD), performance of Broiler Chickens, Feed Conversion